PENDEKATAN DEEP LEARNING DALAM MENGUATKAN PROFIL PELAJAR PANCASILA pada ANAK TK B - Isabella Hasiana; Aisyah Aisyah; Cindy Asli Pravesti; Elisabeth Christiana; Dia Eka Wati (STKIP Pesisir Selatan, 2026)
This study aims to describe the application of a deep learning approach in strengthening the Pancasila Student Profile in kindergarten children. This study is motivated by the importance of meaningful learning from an early age to foster character values, attitudes, and basic competencies in children according to the dimensions of the Pancasila Student Profile. The method used is descriptive qualitative. The subjects of the study were kindergarten children group B and class teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of a deep learning approach through meaningful, reflective, and contextual learning activities can strengthen the dimensions of the Pancasila Student Profile in children, especially in the aspects of faith and noble character, independence, mutual cooperation, and critical reasoning. Children appear more active, responsible, able to cooperate, and dare to express opinions in learning activities. The novelty of this study lies in the implementation of a deep learning approach in the context of early childhood education as a strategy to strengthen the Pancasila Student Profile, which is still relatively limited in qualitative studies.